Material-to-system tailored multilayer-cyclic strategy toward practical atmospheric water harvesting - Yaxuan Zhao; Weixin Guan; Yan Zhe Wong; Chuxin Lei; Yuyang Wang; Xiaomeng Liu; Guihua Yu (Proceedings of the National Academy of Sciences, 2025)
Solar-driven atmospheric water harvesting (AWH) presents a sustainable approach for freshwater production with sunlight as the sole energy input. To address challenges posed by diurnal moisture variations and diffusive sunlight, we present a system-wide approach that synergistically enhances moisture capture and solar energy utilization in an integrated water harvester. Moisture utilization at the bulk sorbent scale is improved through the hierarchical pore structure of scalable biomass gel sheets enabling rapid regeneration and is further upscaled to system-level performance through a kinetics-matched, continuously multicyclic operation protocol in a multilayered device. Solar energy utilization is enhanced by thermoresponsive hydrogels that lower the energy threshold for water desorption and by efficient thermal and mass flow management that increases energy efficiency. Our system delivers up to 235.09 mL d −1 of water with an energy efficiency as high as 26.4%, excluding solar panel power. This work offers an insight into developing energy-, material-, and space-efficient AWH systems from a cross-scale understanding of sorbent properties, device engineering, and operation protocol tailoring.